TINGKAT PERMINTAAN SUKUK RITEL: ANALISIS FAKTOR INTERNAL DAN EKSTERNAL - Rifqi Muhammad; Eka Natha Permana; Peni Nugraheni (Media Riset Akuntansi, Auditing & Informasi, 2019)
Sukuk is one of the investment instruments that attract Muslim investors who want to invest in accordance with sharia principles. The demand for sukuk is relatively high every time a sukuk is issued. The study aims to examine the factors influencing the demand of retail sukuk issued by government. Independent variables consist of sukuk price, BI rate, inflation rate and rate of return of Mudharaba investment accounts.  Retail sukuk SR-005 is choosen as dependent variable because of the highest average investment per investor during ten years of retail sukuk issuance. The data is taken from February 2013 to February 2016 and analysed using panel data regression. The results indicate that BI rate has negative influence on the demand of retail sukuk SR-005 while sukuk price, inflation rate and rate of return of mudharaba investment accounts do not influence the demand of retail sukuk SR-005. This study is expected to contribute to the scientific development of Islamic finance, especially the study of sukuk.